An interface finite element based on a frictional contact formulation with an associative plasticity model for the tangential interaction. (7th February 2017) - Michaloudis, G.; Konyukhov, A.; Gebbeken, N.
Summary: In this contribution, a three‐dimensional frictional contact formulation in the form of an interface solid finite element is discussed. The interface element incorporates normal as well as tangential contact conditions and aims at the modeling of phenomena occurring in engineering problems on the interface between different materials. The focus of this work lies on the description of the tangential interaction of bodies on their contact interface. Instead of the widely used Coulomb friction law, a simple elastoplastic material law is applied in order to model the interaction mechanism on the tangent plane. Appropriate local coordinate systems are introduced on the surface and point of contact, and all contact operations are performed in these coordinate systems by adopting a fully covariant description. In this way, we derive a symmetric element stiffness matrix not only for the case of sticking but also for sliding. Exploiting the advantages of the covariant description, we show that the fact that the derived stiffness matrix discretely consists of constitutive and geometrical parts enables us to introduce rather straightforwardly new appropriate interface laws describing the tangential interaction of the contacting bodies. The presented numerical results show very good correlation of the developed approach with 'pull‐out' experiments. Copyright © 2016 John Wiley & Sons, Ltd.